Comparison of Bayesian Estimation Methods for Rayleigh Progressive Censored Data Under the Different Asymmetric Loss Function - Azimi, Reza; Yaghmaei, Farhad; Azimi, Dariosh (International Journal of Applied Mathematical Research, 2012)
In this paper, given a progressively type II censored sample from a Rayleigh distribution, the Bayesian estimators of parameter and  Reliability function are obtained under asymmetric loss functions such as LINEX loss function, Precautionary loss function, entropy loss function for the parameter and reliability function. Comparisons of these estimators are made through simulation study.